Experimental study temperature evolution of pseudoelastic TiNi alloys during shock-induced phase transformation - Shen, L.; Liu, Y.; Shan, J. (Archives of Mechanics, 2018)
The temperature evolution and the mechanical characteristics of pseudoelasticity TiNi alloys have been studied experimentally at different strain rates. During SHPB testing, the temperature changes were in situ measured by an infrared system recording infrared radiation emitted from the surface of the specimen. It was found that the temperature evolution and the mechanical behavior has a remarkable strain rate effect. With the strain rate increasing, both phase transition subsequent stress and modulus of loading the phase transition stage were higher, exhibiting significant strain and the strain rate hardening characteristic. They were accompanied by the temperature increasing, which suggest that the stress increments result from the temperature change, independently of the strain rate. Calculation analysis results show that latent heat and the dissipated energy in the form of the hysteresis loops, are mainly the sources of the temperature change.